The design of biodegradable ofloxacin-based core-shell microspheres: Influence of the formulation parameters on in vitro characterization - SEZER, ALİ DEMİR (TAYLOR & FRANCIS LTD, 2012)
Ofloxacin (OFL), second-generation fluoroquinolone, is a broad-spectrum antibiotic which is active against both Gram-positive and Gram-negative bacteria. However, OFL has a short biological half life (8-9 h) and poor stability in serum and needs frequently repeated doses during the treatment. The objective of this study was to fabricate the fucospheres and chitosan microspheres containing a poorly soluble drug, OFL, and to compare the formulation parameters influencing the in vitro properties of microparticles such as size, zeta potential, encapsulation efficiency and drug release characteristics. Particle size of fucospheres and chitosan microspheres has been found to be 0.61-1.48 mu m and 1.05-2.08 mu m, respectively. The zeta potentials have changed between 5.6 mV and 28.0 mV for fucospheres; 22.3 mV and 42.4 mV for chitosan microspheres. The fucospheres have had higher drug encapsulation efficiency than those of chitosan microspheres. The particle size, surface charge, encapsulation efficiency and in vitro drug release from both fucospheres and chitosan microspheres have been affected by type and concentration of the polymers used. The release mechanism from most of the microsphere formulations has been fitted to Higuchi kinetic model. It can be concluded that OFL-encapsulated fucospheres can be a potential delivery system for antibiotics.</.
Keywords: CHITOSAN MICROSPHERES; DRUG-DELIVERY; SUSTAINED-RELEASE; NANOPARTICLES; ENCAPSULATION; ENROFLOXACIN; FUCOSPHERE; LIPOSOMES; FUCOIDAN; SYSTEM